Gestão da Informação e do Conhecimento no âmbito da Indústria 4.0: aproximação das temáticas de estudo por análise bibliométrica - Wilmers, Júlia Tereza Abrão Vieira Lourenço (2019)
The Fourth Industrial Revolution emerges on a new world scenario in a scope where connectivity and information exchange gain prominence. More than just a set of technological innovations, Industry 4.0 can be considered a revolution because of the abrupt and radical change in the way society lives and interacts. The greatest challenge of this new era is the intelligent use of data, information and knowledge in strategic decision making, whether by machines or by humans. Thus, Information and Knowledge Management must have attention to this context. In this sense, this research is classified as basic nature and presents a quanti-qualitative approach, with the descriptive-exploratory objective of understanding the approximation between Information Management, Knowledge Management and Industry 4.0 research themes. Moreover, it is observed the research trends in Information and Knowledge Management and their adherence to publications on the emerging theme of Industry 4.0. In this sense, it was used bibliometric techniques with the analysis made through the study of descriptors, keywords and abstract. The choice of the Web of Science database made it possible to retrieve, through the descriptors, 10,890 records for the term Knowledge Management, 6,207 records for Information Management and others 3,304 records for the term Industry 4.0. The VOSViewer© and Microsoft Excel were used for processing and visualization of data, such as the creation of collaboration networks and keywords’ maps. Data were analyzed and presented as: the evolution of publications, collaboration networks between countries, the co-occurrence of keywords through maps. Based on this study, it was possible to identify the similarity of terms in the three great themes, as well as approximate their similar terms of study. As future studies, it is suggested the use of other databases and the search for correlated descriptors from the three themes.